Comparison of crossover and mutation operators of genetic algorithm applied to CSM-UPMin scheduling problem - Talaugon, Armida Glaiza Varquez (2011)
Course timetabling problem is an assignment of lectures to periods and rooms subject to constraints. GA which is inspired by natural evolution in biological systems, the "survival of the fittest" principle of natural evolution by Darwin, is an adaptive which may be used to solve search and optimization problems. Although the genetic algorithm was found to be promising in timetabling courses of the College of Science and Mathematics University of the Philippines in Mindanao, it is still not known which kinds of crossover operators and mutation operators are effective in producing better timetables. Hence, in this study,combinations of different crossover and mutation operators were compared to know which combination produces the best schedule. Results showed that the combination of conflict-based and violation directed is the best among other combinations. The second best, though, is not known in this study. However, these results were not confirmed further by statistical analysis. Although the present results obtained indicate the effectiveness of the violation-directed mutation combined with conflict-based crossover, further studies are still needed to explore the potential of other operators.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2011
Keywords: Genetic algorithm; Scheduling; Scheduling problem; University course timetabling; Crossover; Mutation; Mutation operators; Conflict-based crossover